Value Added Tax and Turnover Tax on Legal Services in Ethiopia: Vexing Questions and Qualms - Alkadir, Mohammode Doude (Bahir Dar University Journal of Law, 2023)
In the current tax system of Ethiopia sales tax is levied and being collected on legal services either by the federal government or the regional governments, on case by case basis, through instrumentality of value added tax and turnover tax. There are, however, vexing questions and qualms related to the legal basis and justifiability of the tax base, rate and the administration thereof. The main objective of this study is designing solutions by qualitatively scrutinizing these vexing questions and qualms. To this end the author made use of documents, interviews and focus group discussions as tools. The study also endeavors to examine the experience of other jurisdictions. The study, as a result, offered three alternative solutions of which the first is maintaining the existing scene by taxing legal services and urging the government to do its best in ensuring justice and protecting constitutional rights. On the other extreme, the study alternatively pleads for the abrogation of sales tax on legal services and its replacement by other revenue sources. As a third alternative, the study urges for the adoption of a graduated sales tax schedule for different categories of legal services. For this purpose the indispensability of the legal service and its nexus to constitutional rights; the clientsâ€™ ability to pay; and the governmentsâ€™ financial need ought to be considered in levying different sales tax rate on different categories of legal services.